2006
DOI: 10.1002/chem.200501217
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Carbenes to the Sidewalls of Single‐Walled Carbon Nanotubes

Abstract: The addition of carbenes CX(2) (X=H, Cl) to single-walled carbon nanotubes (SWNTs) was investigated by density functional theory and finite, hydrogen-terminated nanotube clusters or periodic boundary conditions in conjunction with basis sets of up to polarized triple-zeta quality. For armchair [(3,3) to (12,12)] and zigzag tubes [(3,0) to (18,0)], reaction of CH(2) with the C--C bond oriented along the tube axis (A) is less exothermic than with those C--C bonds having circumferential (C) orientation. This pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
54
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 73 publications
13
54
0
Order By: Relevance
“…[15]) and localized basis calculations (1.4 eV, Ref. [16]). Second, we find that the C 1 -C 6 distance for this O configuration (d 16 in Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[15]) and localized basis calculations (1.4 eV, Ref. [16]). Second, we find that the C 1 -C 6 distance for this O configuration (d 16 in Fig.…”
mentioning
confidence: 99%
“…[16]). Second, we find that the C 1 -C 6 distance for this O configuration (d 16 in Fig. 1(c)) is much larger than the usual C-C distance (1.54Å in diamond and 1.42Å in graphite), a clear indication that the sidewall bond is broken [15,16,17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the B3LYP calculations, both mechanisms are competitive in energy. In addition, Bettinger also analyzed carbene reaction between CCl 2 and a finite-length nanotube, and found that a transition state for the reaction lies only a few kcal/mol above the dissociation limit toward the nanotube and CCl 2 (Bettinger, 2006). Following the previous experimental and theoretical studies, we recently performed extensive DFT calculations to elucidate the stability of 12 configurations of cycloaddition of diethylbutane-2,3-diyl to the outer surface of a nanotube (Yumura & Kertesz, 2009).…”
Section: Site-selective Addition Of a Bismalonate Into Nanotubementioning
confidence: 99%
“…Let us first discuss the addition of carbene into the outer (Chen et al, 2004;Bettinger, 2004;Zhao et al, 2005;Bettinger, 2006;Zheng et al, 2006;Lee & Marzari, 2008) or inner surface of the (5,5) or (10,10) nanotube, whose optimized geometries are seen in Figures 2 and 3. As mentioned above, the divalent atom of carbene binds into a CC bond of sp 2 systems.…”
Section: Addition Of Carbene Into a Nanotube And Concomitant Surfacementioning
confidence: 99%